Análise comparativa de um DNA satélite compartilhado em espécies de peixes Characiformes - Gonçalves, Évelin Mariani (2022)
The centromeric region of the eukaryotic chromosomes is composed of repetitive sequences, being represented mainly by tandem repeats commonly known as satellite DNAs. Studies referring to these highly dynamic sequences have demonstrated their important roles in genomes, especially with regard to genomic evolution, chromosomal composition and species differentiation. Despite their high variability, these sequences may show some conservation among some groups, which makes them attractive for genomic, population and evolutionary studies. Studies referring to the group of fish that address the centromeric composition and possible conservation of satDNAs in this region are scarce and still few explored in recent publications. The present work involved the study of a 177 bp satellite DNA (MelSat03- 177) previously isolated from the genome of the Neotropical fish Megaleporinus elongatus (Order Characiformes) which located in the centromeric region of some chromosomes of the species, in order to analyze the possible conservation of this sequence and to know a few more about its distribution and organization in other fish genomes, mainly in Characiformes. Through a database search, homologous sequences to the satellite MelSat03-177 were retrieved from other species of the Order Characiformes, with a relevant percentage of identity, showing signs of conservation of the sequence. The present work provided initial information, but of great importance for the study of satellites DNA, especially for satDNA in centromeric region, being able to promote several studies related to the distribution, organization and conservation of centromeric repetitive sequences present in the fish group.